The evidence for non-typeable Haemophilus influenzae as a causative agent of childhood pneumonia - Mary P E Slack (Pneumonia, 2017)
Abstract Haemophilus influenzae type b (Hib) was a major cause of bacterial pneumonia in children prior to the introduction of Hib-conjugate vaccines. The widespread use of Hib-conjugate vaccines has resulted in a significant decline in the number of cases of invasive Hib disease, including bacteraemic pneumonia, in areas where the vaccine has been implemented. In many countries, non-typeable H. influenzae (NTHI) is now the most common cause of invasive haemophilus infection in all ages. NTHI are a recognized cause of bacteraemic and non-bacteraemic pneumonia in children and in adults. Less than 10% of cases of pediatric pneumonia are bacteraemic, and children generally do not expectorate lower respiratory tract secretions, so determining the microbial cause of a non-bacteraemic pneumonia is challenging. In this commentary the evidence that NTHI is a cause of pneumonia in children is briefly reviewed.